Mediation Effects of Work Motivation: Self-Efficacy and Patient Safety Culture on Caring Behavior - Zuriyati Ulfa; Agusdini Banun Saptaningsih; Nofierni Nofierni (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Caring behavior increases patient satisfaction, trust, and loyalty, a government indicator to enhance hospital healthcare services. Caring behavior also reduces patient falls by improving safety. However, at Karawang Regional General Hospital, concerns regarding inpatient service quality were reflected in a notable rise in reported issues over a one-year period. This study aims to analyzes how self-efficacy and patient safety culture affect caring behavior and how work motivation acting as an intervening variable. A cross-sectional design was used on 195 inpatient nurses as respondents using simple random sampling. Data were collected using a 31-item 4-point Likert scale questionnaire with 15 indicators. LISREL 8.80 was used to analyze data using Covariance-Based Structural Equation Modeling (CB-SEM). The results show that self-efficacy (β=0.11, t=2.21), patient safety culture (β=0.19, t=3.69), and work motivation (β=0.70, t=9.67) significantly and positively affect caring behavior. Furthermore, self-efficacy and patient safety culture also contribute to increased work motivation, with t-values of 7.48 and 6.98. These findings show that work motivation is the main factor in increasing caring behavior and mediates the relationship between self-efficacy and patient safety culture. Self-efficacy and patient safety culture also boost work motivation.